1999
DOI: 10.1002/1529-0131(199905)42:5<981::aid-anr17>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of mononuclear cells expressing the chemokine receptor CCR5 in synovial effusions of patients with different forms of arthritis

Abstract: The predominance of CCR5-positive mononuclear cells in the synovial effusions of patients with arthritis suggests an important role for CCR5 in the process of joint inflammation, and identifies CCR5 as a possible new target for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
81
2
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 40 publications
10
81
2
1
Order By: Relevance
“…A high proportion of CCR5-positive T cells in RA synovium has also been reported (30,(40)(41)(42)(43). Furthermore, Unutmaz et al (38) showed that IL-15 stimulation increased the number of CXCR6 and CCR5 double-positive CD4 and CD8 T cells in vitro.…”
Section: Discussionmentioning
confidence: 71%
“…A high proportion of CCR5-positive T cells in RA synovium has also been reported (30,(40)(41)(42)(43). Furthermore, Unutmaz et al (38) showed that IL-15 stimulation increased the number of CXCR6 and CCR5 double-positive CD4 and CD8 T cells in vitro.…”
Section: Discussionmentioning
confidence: 71%
“…Only very recently a role for the chemokine receptor CCR5 in RA was confirmed, consistent with the elevated levels of RANTES found in RA patients (64,65). The lymphocytes found in inflamed synovial joints of RA patients are CCR5 ϩ (43,66,67). Studies on individuals with a variable CCR5 genotype revealed clinical amelioration in RA.…”
Section: Figurementioning
confidence: 71%
“…Data on CCR2 expression in humans and results from studies of CCR2-deficient mice (2-4) support the blockade of CCR2 as an effective strategy in the treatment of multiple sclerosis and diabetes. In patients with rheumatoid arthritis, we and other investigators have found an increased frequency of CCR2ϩ cells in the synovial fluid and synovial tissue (5)(6)(7). In addition, increased levels of the CCR2 ligand monocyte chemoattractant protein 1 (MCP-1; CCL2) were found in patients with rheumatoid arthritis (8).…”
mentioning
confidence: 62%